PENGARUH PERMAINAN TWISTER MODIFIKASI TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI ANAK USIA 4-5 TAHUN DI TK SHANDY PUTRA TELKOM KOTA PEKANBARU - Rahmadani, Betria; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on the ability to recognize the shape of the geometry of students has not developed optimally. So it is necessary to apply the game twister modification. The purpose of this study was to examine the effect of twister modification on the ability to recognize geometric shapes of children aged 4-5 years. This research was conducted at TK Shandy Putra Telkom Pekanbaru City during May 2017. The research used experimental method with one group pre-test post-test design design with 15 samples. The data collection technique used in this research is using observation sheet to record about the activities that occurred during the given treatment. Data anlisis technique using t-test by using spss program 18. From result of data analysis obtained tcount equal to 20,579 bigger than t table = 2,145 with sig 0.000 <0.05. It can be concluded that there are differences in the ability to recognize geometric shapes significantly before and after the application of the twister modification game. Based on hypothesis test results obtained there is the effect of twister game modification to the ability to recognize the geometry of children aged 4-5 years in Shandy Putra Telkom kindergarten Pekanbaru City of 61.46%.Keywords: Geometric Shape Recognizing Ability, Twister Modification Game.